2017
DOI: 10.1097/cmr.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive pathologic work-up in sentinel lymph node biopsy for melanoma: is it necessary?

Abstract: The objective of this study is to determine whether a less exhaustive pathologic work-up to detect melanoma metastasis is clinically useful and does not affect patient prognosis. The success and evolution of the sentinel lymph node (SLN) depends on histological techniques. Several exhaustive protocols of SLN analysis have been published, but are time and cost consuming, with slight increases in the rates of metastasis detection. From 281 patients with SLN biopsy, each SLN was sectioned every 2 mm and from each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Currently, institutional protocol for histopathological handling of sentinel lymph nodes and pathological reporting varies widely. 68,128,129,130,131,132 Macroscopically, two main methods of slicing sentinel lymph nodes exists: 'breadloafing', allowing for better examination of the subcapsular region, and bivalving, allowing for better examination of lymphatic vessels. 130,131 Both the European Organisation for Research and Treatment of Cancer (EORTC) and Sydney Melanoma Unit recommend the utilisation of the bivalving technique in sentinel lymph node histopathological and handling protocol.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, institutional protocol for histopathological handling of sentinel lymph nodes and pathological reporting varies widely. 68,128,129,130,131,132 Macroscopically, two main methods of slicing sentinel lymph nodes exists: 'breadloafing', allowing for better examination of the subcapsular region, and bivalving, allowing for better examination of lymphatic vessels. 130,131 Both the European Organisation for Research and Treatment of Cancer (EORTC) and Sydney Melanoma Unit recommend the utilisation of the bivalving technique in sentinel lymph node histopathological and handling protocol.…”
Section: Discussionmentioning
confidence: 99%
“…68 The process of IHC staining, which may augment prognostication, is time-consuming and labourintensive. 128,129 IHC has been shown to mildly increase metastatic tumour detection rates in sentinel lymph nodes, but whether these mild increases justify the time and cost of performing IHC is controversial. 129 One study found that, although extensive IHC work-up may increase detection rates, survival is unaffected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations